2018
DOI: 10.12693/aphyspola.134.688
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium Based Alloys with High Content of Metastable Phases Prepared by Powder Metallurgy

Abstract: In this paper, the results of preparation and mechanical testing of AlFe7Mn4 alloy are presented. The alloy was prepared by rapid solidification (melt spinning) in the form of thin ribbons. The ribbons were compacted by spark plasma sintering in three different ways-whole, cut into stripes, and crushed into powder in a ball mill. Microstructures of compact materials were observed by scanning and transmission electron microscope. Phase composition was characterized using X-ray diffraction. Rapidly solidified ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The rapidly solidified aluminum alloy with the addition of Fe (up to 11 wt. %) is composed of a supersaturated solid solution of Fe in aluminum and metastable Al 6 Fe [17] on the faster-cooling side, while the air side contains a smaller amount of stable Al 13 Fe 4 , also referred as Al 3 Fe [18], and metastable Al 6 Fe. The supersaturated TM elements in our study were confirmed by TEM analyses in Figure 5, where all the nano-precipitates consist of Al, Mn and Fe.…”
Section: Resultsmentioning
confidence: 99%
“…The rapidly solidified aluminum alloy with the addition of Fe (up to 11 wt. %) is composed of a supersaturated solid solution of Fe in aluminum and metastable Al 6 Fe [17] on the faster-cooling side, while the air side contains a smaller amount of stable Al 13 Fe 4 , also referred as Al 3 Fe [18], and metastable Al 6 Fe. The supersaturated TM elements in our study were confirmed by TEM analyses in Figure 5, where all the nano-precipitates consist of Al, Mn and Fe.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, for the case of powder compaction a considerable interface portion provides perfect initial conditions for enhanced diffusivity and, thus, ability to create bulk samples from unjoinable metals, however leaving an open question concerning the purity of the final product. [ 24 ] Diffusion enhancement in case of solid state welding of thin disc samples is much more limited due to the smaller amount of interacting interfaces, but it allows us to obtain a contamination‐free bulk composite.…”
Section: Introductionmentioning
confidence: 99%